Could Chlorella pyrenoidosa be exploited as an alternative nutrition source in aquaculture feed? A study on the nutritional values and anti-nutritional factors - Chen, Fufeng; Qian, Jun; He, Yu; Leng, Yunyue; Zhou, Wenguang (Frontiers in Nutrition, 2022)
This work attempted to identify if microalgal biomass can be utilized as an alternative nutrition source in aquaculture feed by analyzing its nutritional value and the anti-nutritional factors (ANFs). The results showed that Chlorella pyrenoidosa contained high-value nutrients, including essential amino acids and unsaturated fatty acids. The protein content in C. pyrenoidosa reached 52.4%, suggesting that microalgal biomass can be a good protein source for aquatic animals. We also discovered that C. pyrenoidosa contained some ANFs, including saponin, phytic acid, and tannins, which may negatively impact fish productivity. The high-molecular-weight proteins in microalgae may not be effectively digested by aquatic animals. Therefore, based on the findings of this study, proper measures should be taken to pretreat microalgal biomass to improve the nutritional value of a microalgae-based fish diet.